2006
DOI: 10.1007/s00125-006-0184-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte dysfunction in insulin-resistant rats: a female advantage

Abstract: Aims/hypothesis: The goal of this investigation was to determine whether there are sex-related differences in the development of cardiomyocyte dysfunction in prediabetic, insulin-resistant animals. Materials and methods: Male and female rats were maintained on a high-sucrose diet for 5-11 weeks, and mechanical properties of isolated ventricular myocytes were measured by high-speed video edge detection. Several in vitro interventions were used to manipulate intracellular Ca 2+ in order to determine whether alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Experimental evidence suggested that female rats are better protected from hyperglycemic and insulin resistance–induced insult unless they are ovariectomized, consistent with the observation that estrogen alleviates diabetic complications in males (63,64). Estrogen is known to maintain normal adipose tissue biology, liver fatty acid metabolism, and suppression of hepatic glucose production.…”
Section: Gender Insulin Sensitivity Glucose and Lipid Homeostasissupporting
confidence: 77%
“…Experimental evidence suggested that female rats are better protected from hyperglycemic and insulin resistance–induced insult unless they are ovariectomized, consistent with the observation that estrogen alleviates diabetic complications in males (63,64). Estrogen is known to maintain normal adipose tissue biology, liver fatty acid metabolism, and suppression of hepatic glucose production.…”
Section: Gender Insulin Sensitivity Glucose and Lipid Homeostasissupporting
confidence: 77%
“…Myocyte relengthening [A R /PK, TR, and maximum negative length change (Max ϪdL/dt)] was also similar in the ZDF and Lean control groups. The lack of impaired contraction and relaxation in the 6-wk ZDF group was somewhat surprising since insulin resistance (duration Ն7 wk) has been shown to adversely affect cardiomyocyte E-C coupling (29,33). However, at 22 wk of age both contraction and relaxation were significantly impaired in the hyperglycemic ZDF group compared with controls.…”
Section: Resultsmentioning
confidence: 93%
“…The fructose concentration (11 mM) was chosen as an equimolar replacement of glucose to ensure controlled superfusate conditions (this fructose level would not normally be observed in vivo ). The glucose buffer composition was modeled on standard formulations used in previous in vitro studies and the glucose concentration employed is consistent with plasma glucose levels reported for rodents (generally higher than humans) [19], [20], [21]. Myocytes were superfused for 2–3 minutes to obtain steady-state, and measurements of intracellular Ca 2+ and myocyte twitch kinetics were recorded for a 2 min treatment period for each cell.…”
Section: Methodsmentioning
confidence: 99%